Development of Hybrid Solar Photovoltaic and Wind Energy Powered UPS System for Small Loads Supply - Malson, Melveyson; Baharom, Md Ramdon (Evolution in Electrical and Electronic Engineering, 2022)
One of humanity’s greatest desires today is for reliable and sustainable electricity. Conventional, non-renewable energy resources (e.g., coal, nuclear) have been used to generate electricity for many years. However, with constant use, these resources were depleting. This prompted a shift in focus to renewable energy sources such as wind, solar, and tidal energy, among others. As a result, the goal of this project was to Develop a Hybrid Solar Photovoltaic and Wind Energy Powered UPS System for Small Loads Supply using renewable energy sources, namely wind and solar energy, to generate reliable and sustainable electricity. To accomplish this, a wind turbine was built to convert wind energy to electric energy, and a solar panel was built to convert solar energy to electric energy. A hybrid charge controller was also included to "multiplex" the inputs from the turbine and solar panel and provide an output voltage sufficient to charge the 12 V battery. The battery's DC output used to power household DC appliances. The results showed that the wind source is hard to get and only available in certain places in Sabah. In fact, it was lower than what the turbine needed to produce the 12 V DC output needed to power the system. On a brighter note, the results of the solar panel testing revealed that the solar panel was more than capable of producing at least 12 V for many hours, particularly during the day. The study concluded that, while the 12 V DC input required by the system to function would not be available at all times during the day, the use of a 12 V battery as an auxiliary power source extended the time the system was available. As a result, it is possible to conclude that the project’s goal was met.